Metode Pembelajaran PAUD Berbasis Islam Tradisonal Salafi : Studi terhadap Penerapan Perkembangan Kognitif di TK Islam Yaa Bunayaa Kota Palembang - Marfina Damayanti; Muhtarom Muhtarom; Elsa Cindrya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of learning methods on the cognitive development of children at Yaa Bunayya Islamic Kindergarten. The research adopts a qualitative approach using a case study design to gain an in-depth understanding of how learning methods are implemented to support children’s cognitive growth. Data were collected through direct observation, in-depth interviews with teachers, and documentation analysis of learning activities. The findings reveal that the kindergarten applies five main learning methods, namely habituation, gradual instruction, practice-based learning, talqin (guided repetition), and singing. These methods are implemented systematically to stimulate children’s cognitive abilities in a more optimal and structured manner. Through daily routines and consistent learning activities, children demonstrate positive cognitive development that aligns with established child development indicators, including understanding concepts, memory improvement, and problem-solving skills. In addition, the learning system at Yaa Bunayya Islamic Kindergarten has distinctive characteristics compared to conventional kindergartens. Certain activities such as singing and clapping are applied selectively, teachers’ dress codes reflect Islamic values, and routine activities are conducted before classroom learning begins to prepare students mentally and emotionally. Overall, the combination of structured methods, religious values, and consistent routines contributes significantly to supporting children’s cognitive development in a holistic and effective learning environment.